Pengaruh Stres Kerja dan Kompensasi terhadap Kinerja Karyawan pada CV Arwana Mas Palembang - Yulianti, Nyayu Apni; Marnisah, Luis; Roswaty, Roswaty (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
This study aims to investigate the effects of work stress and compensation on employees' performance at CV Arwana Mas Palembang. Data of 60 respondents were collected through a questionnaire. This study implemented the multiple linear regression method to analyze the data. The results of the investigation show that partially work stress has no significant effect on employees' performance. Conversely, compensation has a significant and positive effect on employees' performance. This empirical evidence can provide benefits for CV Arwana Mas Palembang. To improveemployees' performance, the leader of the company should the neglect work stress factor but optimize compensation for their employees.